2015
DOI: 10.1088/1054-660x/26/1/015602
|View full text |Cite
|
Sign up to set email alerts
|

LED and low level laser therapy association in tooth bleaching using a novel low concentration H2O2/N-doped TiO2bleaching agent

Abstract: Since low concentration bleaching agents containing N-doped TiO2 nanoparticles have been introduced as an alternative to conventional agents, it is important to verify their efficacy and the hypersensitivity effect in clinical practice. Six volunteer patients were evaluated for color change and hypersensitivity after bleaching using 35% H2O2 (one session of two 12 min applications) and 6% H2O2/N-doped TiO2 (one session of three 12 min applications) and after low level laser therapy application (LLLT) (780 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…These findings are consistent with studies reporting that addition of TiO 2 to low-concentration (6% HP) bleaching gels yield similar or better results than higher concentration (35% HP) bleaching agents. 17,49,50 We can explain this situation as follows: TiO 2 activation with a suitable light source accelerates the reaction in the experimental bleaching gel, and free radical production is increased with the increase in the number of applications of the gel on the tooth surface. 17,51 Adding chitosan to the test gel increases the adhesion of the gel to the tooth surface, 52 and HP stabilizes when it comes into contact with air.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with studies reporting that addition of TiO 2 to low-concentration (6% HP) bleaching gels yield similar or better results than higher concentration (35% HP) bleaching agents. 17,49,50 We can explain this situation as follows: TiO 2 activation with a suitable light source accelerates the reaction in the experimental bleaching gel, and free radical production is increased with the increase in the number of applications of the gel on the tooth surface. 17,51 Adding chitosan to the test gel increases the adhesion of the gel to the tooth surface, 52 and HP stabilizes when it comes into contact with air.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major undesirable effects of bleaching is tooth sensitivity [ 4 , 7 , 9 , 12 , 13 , 15 – 18 ] that occurs during and after the treatment and may represent a degree of biological damage to the dentin-pulp complex [ 4 , 7 , 9 , 13 , 15 – 17 ]. There are many factors that are known to increase sensitivity, such as high concentrations of H 2 O 2 , high enamel permeability, prolonged use of bleaching agents, heat during application through accelerator lamps, and differences in the structural morphology of enamel and dentin with pores which facilitate the infiltration of bleaching [ 8 , 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to increase both efficacy and safety, new bleaching agents with lower concentrations of H 2 O 2 based on the catalytic action of a nanoparticle semiconductor additive such as titanium dioxide (TiO 2 ) activated by light sources [ 9 , 16 – 20 ] are now entering the market [ 4 , 9 , 13 , 16 – 20 ]. A significant reduction in the sensitivity of bleaching treatments which use nitrogen doped titanium dioxide and 15% H 2 O 2 concentration has been reported in the literature [ 8 , 9 , 16 – 18 ]. Nevertheless, bleaching agents with 6% H 2 O 2 /N-doped TiO 2 are innovative and significantly lower in peroxide concentration and, to our knowledge, there are few clinical studies evaluating in-office tooth bleaching with agents at this concentration [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bortolatto et al reported greater efficacy and a reduction of 52% in the occurrence of tooth sensitivity when the bleaching agent of 15% hydrogen peroxide containing TiO_N was used compared to 35% hydrogen peroxide [20]. More recently, a bleaching agent with concentration even lower, 6% hydrogen peroxide containing TiO_N nanoparticles, has been studied [4,31,32]. Martin et al (23) evaluated the efficacy of this new bleaching agent with 6% of hydrogen peroxide containing TiO_N [24].…”
mentioning
confidence: 99%